Application of PBL in combination with the SP teaching method in the clinical teaching of orthopedics and traumatology - An-Yu Wang; Hao Cheng Zhao; Yue Wei Song; Bing Lang Xiong; Zi Yan Guo; Xu Dong Sun; Ya Xin Pan; Wei Dong Sun (BMC Medical Education)
Abstract Background Standardized training for orthopedic and traumatology residents is a crucial component of postgraduate medical education. Traditional teaching methods, such as Lecture-Based Learning (LBL), often fail to stimulate student initiative and clinical thinking. To address this, our study aimed to explore the effectiveness of a combined Problem-Based Learning (PBL) and Standardized Patients (SP) teaching method in enhancing the clinical skills and self-learning abilities of orthopedic residents. Methods A randomized controlled trial was conducted with 59 orthopedic residents from three medical institutions in China. The participants were randomly divided into a control group (n = 29) receiving traditional LBL combined with SP and a study group (n = 30) receiving PBL combined with SP. Both groups were instructed on common orthopedic diseases for 21 h. Teaching effectiveness was assessed through self-designed electronic questionnaires, classroom performance metrics, and final exams. Results Compared with the control group, the study group demonstrated significantly greater levels of self-study initiative, teamwork ability, classroom learning efficiency, learning interest, and clinical processing ability (P < 0.05). The study group also showed greater improvement in their ability to handle clinical problems and had higher postclass knowledge retention and learning interest scores (P < 0.05). Practical exam scores and overall scores were significantly higher in the study group (P < 0.05), although written exam scores did not differ significantly. Conclusions The combined PBL and SP teaching method was found to be superior to traditional LBL in improving the clinical skills and self-learning abilities of orthopedic residents. This approach enhances student engagement, clinical thinking, and overall educational outcomes, suggesting that it is a valuable addition to orthopedic resident training programs.